(Research on Substitution of Tempe Flour in Snack Puff Extrusion) - Elly Nurlaelyah (Balai Besar Industri Agro, 1997)
The research was aimed at studying the substitution rate of tempe flour for corn flour in the product of snack extrusion. The preliminary study was conducted to find out the suitable rate of tempe flour substitution. The following percentages were used : 5, 10, 15, 20, 25, %. The results of these 5, 10, 15 % were used in the main study. Proximate chemical analysis and organoleptic test were conducted on the snack extrusion produced. The result showed that the use of tempe flour is acceptable to 10% substitution.